Becoming the Divas of SUS: the construction of a community of active women in a socially vulnerable context - Ferreira, Heidi Jancer [UNESP]; Drigo, Alexandre Janotta [UNESP]; Kirk, David (Routledge Journals, Taylor & Francis Ltd, 2021)
Given the rapid growing number of the ageing population worldwide, it has been questioned how health and wellbeing in old age can be improved, especially for women in socially vulnerable contexts. Research have shown that social aspects are key determinants for older-age groups' engagement in an active life. It is crucial to understand older people's experiences with physical activity in order to develop interventions that contribute to health promotion beyond disease prevention. The study's purpose was to explore the experiences of middle-aged and older socially vulnerable women with physical activity within a public-funded programme under the Sistema unico de Saude - SUS [Brazilian public healthcare system]. The study involved a Health and Physical Education professional and 16 women (43-66y) who regularly attended the programme. Data were generated through condensed fieldwork, employing semi-structured interviews and non-participant observation of sessions. Drawing on salutogenesis theory and a critical gender perspective, a qualitative analysis was conducted using the constant comparative method. From the women's experiences, a major finding was the construction of a community of active women, which served as a collective resource to support them in the process of health development. Relating to the emerging community, another three themes were developed. The first was dancing and challenging the gender order, referring to women's experiences of negotiating a collective identity and disrupting the invisibility of their bodies. The second was the HPE professional's dialogical pedagogies as emancipatory, revealing the ways in which the community was supported. The third was the empathetic relationships among the women as a way of coping, representing the women's positive experiences of social support, connectedness and resilience. The findings supported the conclusion that there are promising possibilities for research and practice in socially vulnerable contexts to widen the contributions to health promotion that are not limited to exercise prescription.
Keywords: Health promotion; community-based programmes; exercise; gender; older people